On the symplectic reduced space of three-qubit pure states - Molladavoudi, Saeid (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
Given a specific spectra of single-particle reduced density matrices of three qubits, the singular symplectic reduction method is applied to the projective Hilbert space of tripartite pure states, under the local unitary group action. The symplectic structure on the principal stratum of the symplectic quotient is obtained. A criterion from which the elements of the local normal model of the principal stratum can be constructed up to an equivalence relation and also the components of the reduced Hamiltonian dynamics on it are investigated. It is discussed that other lower dimensional strata are isolated points and so they are the fixed points of every reduced Hamiltonian flow on the original manifold.